Surgical Measurement of the Sphenoid Sinus on Sagittal Reformatted CT in the Turkish Population - Kaplanoglu, Hatice (Eurasian J Med, 2013)
OBJECTIVE: The objectives of this study were to determine sinus measurements specific for the Turkish population using CT sagittal thin-slice reconstruction images and to clarify the three-dimensional anatomical features of the sphenoid sinus, along with its surrounding structures, that are relevant to performing an endoscopic sphenoidotomy. MATERIALS AND METHODS: Images of 300 patients (165 female, 135 male) were studied. The research was conducted on the axial plane with a 1 mm slice thickness and a 0.6 mm slice interval, and sagittal reconstruction was performed with a 0.4 mm slice interval. Measurements of the sinus were obtained, and the presence of Onodi cells was researched. RESULTS: Line 1 was found to be significantly shorter in the Turkish patients of this study compared to studies of other populations. Lines 4 and 6 were found to be longer on the left side (Line 4 right: 18.8±3.6 mm, left: 19.3±3.4 mm, p=0.027; Line 6 right: 24.1±6.8 mm, left: 24.3±6.8 mm, p=0.008). Lines 2, 3, 4 and 6 were longer in men than in women (p<0.05). CONCLUSION: In the Turkish population, Line 1 is shorter, so the risk of skull base perforation is greater. Lines 4 and 6 are longer on the left side; thus, choosing the left ostium in sinus dilation is safer. Because of sex differences regarding Lines 2, 3, 4 and 6, sex should be considered in sphenoid sinus procedures.